Measure of Semantic Likeness Among Business Process Activities in a Telecommunication Company - Sepulveda-Rojas, J; Galvez-Manriquez, D; Espinoza-Perez, A; Vargas-Guzman, M; Fuertes-Sanchez, G (Institute of Electrical and Electronics Engineers Inc., 2020)
The study proposes a measure of semantic similarity to solve the wide variety of business process recovery problems, these measures allow to compare the processes of business models useful for reuse, redesign or reengineering process. A metric that demonstrates the similarity between a reference model or fragment of it is proposed. These metrics focus on the activities that make up a business process and are developed through three measures: syntactic, linguistic and semantic similarities. The results show that the proposed measure is suitable for reuse purposes in manufacturing processes, being a useful tool in the area of knowledge management and process administration. © 2013 IEEE.